Determination of Total Mercury in Solid Samples by Anodic Stripping Voltammetry - Thuong Thi Kim Nguyen; Huyen Thu Luu; Loi Duc Vu; Thao Thi Ta; Giang Thi Huong Le (Journal of Chemistry)
The anodic stripping voltammetry (ASV) was investigated to determine total mercury in solid samples using a gold electrode. The mercury was deposited on the gold electrode in a preconcentration step. The oxidation peak of mercury was irreversible. The optimal conditions of the procedure were found to be as follows: 0.05 mol L−1 HCl solution, deposition potential −0.5 V vs. Ag/AgCl/KCls, deposition time 40 s, and sweep rate 0.04 V s−1. Under the optimal conditions, the peak current showed a linear dependence on Hg2+ concentration in the range from 0.01 to 0.1 mg l−1. The detection limit and quantification limit were 4.28 µg L−1 and 12.98 µg L−1, respectively. The mean recovery and relative standard deviation were 91.2% and 2.4% (n = 9). The procedure was successfully applied for determining total mercury in samples collected from Hanoi light bulb warehouse—The Rang Dong Light Source and Vacuum Flask JSC. The results were compared with cold vapor atomic absorption spectrometry (CV-AAS).